Design of compact wideband unequal wilkinson power divider with improved isolation - Ravi, V; Sharma, Dinesh; K, Purnima; Vummadisetty. Naidu, Praveen; Ravi Raja, A; Kumar, Arvind; P. Singh, Abhaya; Raveendra, P (International Journal of Engineering and Technology, 2018)
In this article, a compact unequal, planar Wilkinson power divider with ultra-wideband operation is proposed. The composed power divider having the size of 11.6 mm Ã— 18.5 mm. It consists of one input and two output branches with individual resistive values. Two isolation resistors are used to provide better isolation between the two output ports. The impedance values of each transmission branch and isolation resistors is varied based on the output power division ratio i.e. (P2/P3). The ADS package simulated results of the designed unequal WPD satisfy the operating range (S11 â‰¤ -10 dB) from 2.5 GHz to 18 GHz and isolation are obtained over the entire frequency of operation.Â